At War in Swaddling Clothes: Stirner’s Unique One as a Conative Existence - Galanopoulos, Kostas (Conatus - Journal of Philosophy, 2021)
In its simplest and primary sense, conatus is about self-preservation. It further involves the obligation, the duty, the imperative even, deriving from the Law of Nature for man to do whatever within his power to maintain his life. Even though this idea has been an old one, it was reintroduced in a more sophisticated form by modern philosophy as no longer a cruel necessity of life but ontologically tied to Reason and Natural law. It was with Hobbes that the idea of self-preservation was put at the core of his anthropological narration (with well known political connotations) and with Spinoza that conatus was delved into within his ontological universe. Regardless of their ontological starting points, both philosophers ended up eventually in a resolution with regard to that primary anthropological tension between individuals, whether this was a common legislator, the political society or the state. Somewhat radical at the beginning, Hobbes and Spinoza had to make some mitigations in order to arrive at a resolution. Yet, that was not Stirner’s case. On the contrary, Stirner’s opening ontological statement was rather too extreme and inconceivable even: it is also the newborn child that gets to war with the world and not only the other way around. It is the purpose of this paper to argue that this extreme trailhead leads the Stirnerian egoist to his fulfillment as the Unique One through ownership and that this agonistic tremendous striving constitutes the Stirnerian notion of conatus. That notion offers no resolution to the ontological animosity between individuals; on the contrary, that animosity is required as ontological precondition and prefiguration of conatus’ conclusion as well.